2021
DOI: 10.3390/polym13071031
|View full text |Cite
|
Sign up to set email alerts
|

Fully Polymeric Distillation Unit Based on Polypropylene Hollow Fibers

Abstract: Access to pure water is a very topical issue today. Desalination represents a promising way of obtaining drinking water in areas of shortage. Currently, efforts are being made to replace the metal components of existing desalination units due to the high corrosivity of sea water. Another requirement is easy transportation and assembly. The presented solution combines two types of polymeric hollow fibers that are used to create the distillation unit. Porous polypropylene hollow fiber membranes have been used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Such production is relatively simple, with no waste material produced. The polypropylene hollow-fiber membranes are naturally hydrophobic and have been used in various mainly liquid treatment applications including water/wastewater treatment, membrane bioreactors/contactors [ 19 ], membrane distillation [ 20 ], and medicine/biochemical laboratory uses.…”
Section: Methodsmentioning
confidence: 99%
“…Such production is relatively simple, with no waste material produced. The polypropylene hollow-fiber membranes are naturally hydrophobic and have been used in various mainly liquid treatment applications including water/wastewater treatment, membrane bioreactors/contactors [ 19 ], membrane distillation [ 20 ], and medicine/biochemical laboratory uses.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike pressure-driven desalination processes where spiral wound membranes are state-of-the-art, hollow fiber formats are being considered extensively for FO applications [ 120 , 121 , 122 , 123 , 124 ]. The hollow fiber configuration allows high surface area to volume ratios and, therefore, high overall productivities [ 125 , 126 ], which help to counter flux decline due to polarization effects and fouling. Some of the materials used to fabricate the hollow fiber FO membranes via the traditional dry-jet wet-quench method include polyethersulfone (PES), sulfonated polyphenylenesulfone (sPPSU), and cellulose acetate butyrate (CAB) [ 127 , 128 , 129 ].…”
Section: Modification Strategies Of Fo Membrane Substrates With ...mentioning
confidence: 99%
“…Although PP exhibits comparatively low hydrophobicity, previous investigations have indicated that PP exhibits the best performance in MD due to its physical-chemical stability and easy processing [25][26][27][28]. Polypropylene (PP) is a semicrystalline polymer with a surface energy reaching 30.0 × 10 3 N/m, which provides enough hydrophobicity for the microporous membrane applied to the MD process [29][30][31]. Considering sufficient handling capacity as well as the limits on the dimensions and mass for space applications, a homogeneous PP hollow fiber membrane with a high surface area to volume ratio was fabricated by melt-spinning and stretching in this study.…”
Section: Membrane Fabrication and Characteristicsmentioning
confidence: 99%